Proteze za osebe po amputaciji obeh zgornjih udov - Burgar, Matej (Rehabilitacija (Ljubljana), 2017)
Introduction: Upper limb amputations are much less frequent than lower limb amputations. Their exact number is not known because the majority of countries do not have a registry of amputees. The number of bilateral upper limb amputations is also unknown. The consensus in the literature is that bilateral upper limb amputees need prostheses. The higher is the amputation level, the fewer are the options for socket provision. There are passive and active prostheses available. The passive ones mainly serve aesthetic purpose, even though they are often helful in various activities. The aim of our study was to establish which types of prostheses are used by persons after bilateral upper limb amputation in Slovenia, and which activities do they use them for. Methods: We examined the medical records of all the persons after bilateral upper limb amputation who visited our outpatient clinic for rehabilitation of persons after upper limb amputation and hand prosthetics at least during the the years 2010 % 2015. Results: During the studied five years, seven persons with bilateral amputation had visited our outpatient clinic; they were aged from 16 to 53 years. The reason for amputation was injury in all the cases. Everyone received prostheses except one blind person. After fitting the first prosthesis and completed rehabilitation, they were using the prostheses for one to 12 hours per day. Everyone received sockets for personal hygiene and feeding. Five persons were referred to the outpatient clinic for drivers with special needs. Conclusion: Like elsewhere, there are very few people with bilateral upper limb amputation in Slovenia. For their rehabilitation to be successful, they should all have the opportunity to be fitted with a myoelectric prosthesis, which means that provision of a myoelectric prosthesis for persons after bilateral upper limb amputation should be guaranteed by the compulsory health insurance.
Keywords: amputacija; amputation; avtomobile driving; prostheses; Prostheses and Implants; proteza; rehabilitacija; Rehabilitation; upper limb; vocational rehabilitation; vožnja avtomobila; zgornji ud